George Grant and the Subversion of Modernity : Art, Philosophy, Religion, Politics and Education. - Davis, Arthur (University of Toronto Press, 1996)
The focus of this book is the unknown George Grant, namely, the philosophic, religious, and artistic inspiration behind his well-known public postions.